PROSPECTS FOR THE DEVELOPMENT OF THE EDUCATIONAL ENVIRONMENT: RESULTS AND GUIDELINES OF A QUESTIONNAIRE SURVEY OF TEACHING STAFF AT THE UNIVERSITY - V. A. Persianov; V. V. Borisova; A. V. Kurbatova (Вестник университета)
The analysis of the results of a questionnaire survey of heads of institutes, departments and members of Academic board of the State University of Management on a set of issues related to goal-setting in teaching managerial personnel has been presented. It has been revealed, on the one hand, a variety of respondents ‘ points of view, on the other hand, the presence of a sufficiently high degree of unanimity in goal-setting and ways of exit of the University to the trajectory of effective development. It has been concluded, that it is necessary to take serious measures to improve the quality of higher education using, first of all, rich domestic experience and strategic guidelines in the socio-economic development of the country.